The Influence of Work Motivation, Competence and Compensation on Employee Performance through Job Satisfaction (Literature Study on Domestic Aviation Companies in Indonesia) - Theresia Oktavia Sadipung; I Dewa Ketut Kerta Widana; Primadi Candra Susanto (Dinasti Publisher, 2026)
The domestic aviation industry in Indonesia demands high employee performance because it operates in a high-risk environment with strict safety and service standards. This study aims to analyze the influence of work motivation, competence, and compensation on employee performance through job satisfaction in domestic airlines in Indonesia. The study used a qualitative approach with a literature study method through searching for scientific articles in accredited national journals and reputable international journals relevant to the topic of human resources and the aviation industry, totaling 30 article references. Data analysis was conducted using content analysis and thematic synthesis techniques to identify patterns of relationships between variables. The results of the study indicate that work motivation, competence, and compensation have a direct effect on employee performance and an indirect effect through job satisfaction. This study provides a conceptual contribution in the form of an integrative model of human resource management that emphasizes the importance of psychological dimensions and employee well-being in improving the operational performance of domestic airlines in a sustainable manner.